"Recent Field Research in Folk Music and Folk Dance: Aims and Methods.” (International Library of African Music, 1969)
One of the main themes for discussion at the twentieth International Folk Music Council Conference, which this year will be held in August at Edinburgh, will be "Recent Field Research in Folk Music and Folk Dance: Aims and Methods.” The results of these discussions should be of interest to all members of the African Music Society in view of the recent developments and progress with the text-book Project proposed and piloted by Dr. Hugh Tracey of the I.L.A.M.
Keywords: African Music